Pathogenic Mechanisms of Depression in Multiple Sclerosis - Vattakatuchery, Joe John; Rickards, Hugh; Cavanna, Andrea Eugenio (The journal of neuropsychiatry and clinical neurosciences, 2011)
This article reviews various theories and findings on mechanisms of depression in MS, describing the latest research approaches, as they relate to theories of disease-process. The authors have compiled data on lesion location, extensity, and severity; the effects of immune dysfunction and side effects of immunomodulatory drugs, including interferon therapy; and psychosocial stressors as they all relate to the common symptom of depression in MS. Patients with multiple sclerosis (MS) have an increased risk of developing depression as compared with healthy subjects and patients with many other chronic neurological conditions. The observation that depressive symptoms can precede the onset of neurological symptoms suggests that depression may be related to early disease-specific processes. Several pathogenic mechanisms have been proposed to explain the etiology of depression in patients with MS. This article reviews the current evidence for the contribution of lesional, autoimmune, iatrogenic, and psychosocial factors. It appears that the etiology of depression is multifactorial and varies in individual patients with MS.